Análise teórica do potencial antibacteriano de peptídeos oriundos da clivagem in silico da Eritropoetina humana - Perini, Flávio Maurício (2013)
The relationship established between the micro-organisms disease causing and humanity has a long history, the bacteria being one of the main causative agents of disease in humans, some easily controlled others less, usually through the use of antibiotics, however, with the passage of time, the emergence and spread of bacterial resistance to the use of such medications has become a growing concern. In the face of negative perspectives caused by multi-resistance, investment in research that allows the obtaining of new drugs has become a necessity, however, even the pharmaceutical companies had been dynamic, the search for new anti-bacterials has not accompanied the development of multidrug resistance. Therefore, the development of new strategies to combat this growing resistance have received more attention, and antibacterial peptides (PAMs) arise as a perspective. Many PAMs have been isolated from animals and plants showing proven effectiveness. Beyond directly isolated from various organisms, another possibility of obtaining PAMs is design artificial synthesis of peptides or the use of peptides obtained from the fragmentation of organic molecules in the biological composition existing in the standard of living beings. Computational modeling allow choices of peptides more effectively and that may have an effective combat against multidrug-resistant micro-organisms, thus, the development and validation of techniques that use bioinformatics to facilitate the discovery of these PAMs and minimize search costs are excelling in the biotechnology field. In this work, we selected the human erythropoietin protein (EPO) to obtain PAMs through simulations in silico. The peptides were evaluated and tested in different computational models aimed at predicting possible antibacterial effects, considering a possible synthesis for future testing, with the prospect that these agents act as new weapons against the constant evolution of bacterial resistance, since there do not generate immune responses of rejection, allergenicity and cytotoxicity when used in therapies.